Analisis Efisiensi Penggunaan Mesin Produksi Kakao Overall Equipment Effectiveness (OEE) Studi Kasus Pada PT. XYZ - Weipsa, Saul; Soll, Yekson; Awom, Titia Erika Sarlota (Jurnal Sains dan Teknologi (JSIT), 2026)
The cocoa processing industry in Indonesia faces increasing challenges in maintaining production efficiency due to fluctuations in cocoa bean prices, rising operational costs, and stricter product quality requirements. One of the main issues encountered by cocoa processing companies is the occurrence of unplanned machine downtime, extended setup times, and the potential for product defects, all of which directly affect productivity and overall profitability. This study aims to analyze the efficiency of cocoa production machinery utilization at PT. XYZ, an Indonesian cocoa processing company, and to identify the primary sources of inefficiency in order to formulate sustainable improvement recommendations. This research employs a quantitative approach using a case study method. The analysis techniques applied include Overall Equipment Effectiveness (OEE), Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), and machine utilization ratios. The study focuses on key production machines, namely the cleaner–winnower, alkalizer roasting machine, fuel end unit, and liquor tank, based on realistic hypothetical data that represent daily operational conditions. The results indicate that the OEE value of the roasting machine reaches 79.28%, consisting of an availability rate of 81.25%, a performance rate of 100%, and a quality rate of 97.44%. This OEE level remains below the industry benchmark of 85%, with unplanned downtime and setup losses identified as the dominant contributors to inefficiency. These findings suggest that implementing preventive maintenance, optimizing setup time through the Single-Minute Exchange of Dies (SMED) approach, and enhancing real-time quality control can significantly improve machine productivity and support the long-term profitability of PT. XYZ amid volatile cocoa market conditions.